EKSISTENSI JEMAAT AHMADIYAH DI KELURAHAN KENANGA KECAMATAN CIPONDOH KOTA TANGERANG - Nuhrison M Nuh (Harmoni, 2014)
This study focuses on the Jemaah Ahmadiyah Indonesia (Indonesia Ahmadiyah Community) in Kenanga Village, Cipondoh Subregency, Tangerang. While the existence of the JAI community has been questioned by many in Indonesia, this is not the case in Kenanga Village. In this village, JAI is well accepted by the local community. Several factors have led to this integration. First, local religious leaders have an attitude of tolerance and respect for diversity and inclusivity. Second, there are kinship relations between the two communities. Third, the local government has provided protection. Fourth, there is a high level of local public education. Fifth, the Ahmadiyah are involved in a variety of social and religious activities. To maintain the favorable conditions in Gondrong (Kenanga), this article suggests that the tolerant, open and inclusive attitudes of religious leaders must be maintained. The Government of Tangerang City should not submit to the pressure of militant groups who seek to disband Ahmadiyah. They should alsokeep in touch and interact with the local community and religious leaders.